The role of routine nasolacrimal sac biopsy during endoscopic dacryocystorhinostomy. (23rd May 2019) - Banks, Catherine; Scangas, George A.; Husain, Qasim; Hatton, Mark P.; Fullerton, Zoe; Metson, Ralph
Abstract : Objectives/Hypothesis: Most patients who undergo endoscopic dacryocystorhinostomy (DCR) have a diagnosis of idiopathic nasolacrimal duct obstruction. The purpose of this study was to examine the impact of routine biopsy of the lacrimal sac performed at time of DCR on subsequent patient diagnosis and treatment. Study Design: Retrospective review. Methods: The histopathology of nasolacrimal specimens (n = 769), obtained from 654 consecutive patients undergoing endoscopic DCR by a single surgeon over a 30‐year period, were reviewed. Specific focus included the identification of unanticipated pathologic findings as they related to pertinent patient demographics, clinical presentation, radiologic findings, and intraoperative observations. Results: The study population was 69.6% female, with an average age of 56.1 ± 18.2 years. Pathological findings of tissue from the nasolacrimal sac, which was routinely sampled in all cases, showed inflammation (n = 566 [73.6%]), normal histology (n = 147 [19.1%]), granulomas (n = 8 [1.0%]), and neoplastic process (n = 7 [0.9%]). Patient history, preoperative CT scan, and/or intraoperative findings alerted the surgeon to the possibility of an unusual diagnosis in 12 of the 15 patients. An unsuspected neoplastic or granulomatous cause of lacrimal obstruction was identified on intraoperative biopsy in three patients (0.46%). Conclusions: Although neoplastic and granulomatous diseases are relatively rare causes of lacrimal obstruction necessitating DCR surgery, they may be identified by through patient evaluation in most cases and by routine intraoperative biopsy of the lacrimal sac in all cases. Level of Evidence: 4 Laryngoscope, 130:584–589, 2020